Competing on good politicians - Vincenzo Galasso; Tommaso Nannicini (Institute for the Study of Labor (IZA), 2009)
Is electoral competition good for political selection? To address this issue, we introduce a theoretical model in which ideological parties select candidates between party loyalists and experts, and allocate them into the electoral districts. Non-ideological voters, who care about national and local policies, strongly prefer experts. We show that parties compete on good politicians by allocating them to the most contestable districts. Empirical evidence on Italian members of parliament confirms this prediction. We find that politicians with higher ex-ante quality - as measured by years of schooling, previous market income, and local government experience - are more likely to run in a contestable district. Indeed, despite being different on average, the characteristics of politicians belonging to opposite parties converge to high-quality levels in close races. Furthermore, politicians elected in contestable districts make fewer absences in parliament; this is shown to be driven more by a selection effect than by reelection incentives.
urn:nbn:de:101:1-2009082147
Keywords: D72; H00; 330; Political competition; political selection; probabilistic voting; Politiker; Qualifikation; Wettbewerb; Wahl; Wahlverhalten; Italien